Prognostic factors for recurrent instability in recreational athletes following arthroscopic Bankart repair: a retrospective study with an average 4.1-year follow-up - Chunsen Zhang; Songyun Yang; Jiapeng Wang; Wenze Shao; Yizhou Huang; Xin Tang (BMC, 2024)
Abstract Background Extensive research has been conducted to investigate the short-term and long-term outcomes of arthroscopic Bankart repair, yielding varying results across different populations. However, there remains a dearth of studies specifically focused on evaluating outcomes in recreational athletes. Methods A retrospective case series study was conducted on recreational athletes who underwent isolated arthroscopic Bankart repair between 2013 and 2021. The primary outcome assessed was recurrent instability, defined as dislocation or subluxation. Secondary outcomes included patient satisfaction, rates of returning to the same sports (RTS) and RTS at preinjury level, and patient-reported outcomes. Evaluation of the Rowe score, Constant score, American Shoulder and Elbow Surgeons score, and VAS pain score were performed. Prognostic factors for recurrent instability, including demographic and clinical characteristics, as well as postoperative magnetic resonance imaging (MRI) appearance of the labrum were analyzed. Results A total of 191 patients met the selection criteria, with 150 (78.5%) available for the final follow-up. Recurrent instability occurred in 10.7% of patients, with a mean follow-up duration of 4.1 years. Younger age at surgery and more critical glenoid bone loss were significantly associated with recurrent instability (p = .038 and p = .011, respectively). The satisfaction rate regarding surgery was 90.0%. Rates of return to the same sports (RTS) and RTS at preinjury level were 82.0% and 49.3%, respectively. Clinical outcomes measured at the final follow-up were as follows: Rowe score − 92.8; Constant score − 98.0; ASES score − 98.3; VAS pain score − 0.2. Patients with recurrent instability had significantly inferior outcomes in terms of satisfaction rate, RTS at preinjury level rate, Rowe score, and Constant score (p = .000, p = .039, p = .000, and p = .015, respectively). A total of thirty-seven patients underwent MRI examination six months after surgery in our institution. The T2-weighted anterior labrum morphology was found to be poorer in patients with recurrent instability. No significant difference was observed between patients with or without recurrent instability in terms of anterior Slope, anterior labral glenoid height index (LGHI), inferior Slope, inferior LGHI, and T2-weighted inferior labrum morphology. Conclusion Arthroscopic Bankart repair can yield satisfactory medium-term outcomes for recreational athletes. Younger age at surgery, more critical glenoid bone loss, and poorer T2-weighted anterior labrum morphology assessed six months postoperatively were significantly associated with recurrent instability.